Особенности выбора базовых операций при построении симметричных блочных шифров - Елисеев, Р.; Олейников, Р. В. (ХНУРЕ, 2019)
Block cipher algorithm can be created from wide range of operations. The main limitation – it must be present on all target platforms or implementer must be able to efficiently emulate it. Despite large amount of instructions in modern CPUs only few of them used in mainstream ciphers. Its addition, rotation, XOR and array (table) indexing mainly. But many of practical ciphers combines them with additional data manipulations to achieve better performance and/or security.
Keywords: блочный шифр; побитовая операция; возведение в степень; дискретный логарифм